Cardiac CT angiography for device surveillance after endovascular left atrial appendage closure - Saw, Jacqueline; Fahmy, Peter; DeJong, Peggy; Lempereur, Mathieu; Spencer, Ryan; Tsang, Michael; Gin, Kenneth; Jue, John; Mayo, John; McLaughlin, Patrick; Nicolaou, Savvas (European heart journal cardiovascular imaging, 2015)
Left atrial appendage (LAA) device imaging after endovascular closure is important to assess for device thrombus, residual leak, positioning, surrounding structures, and pericardial effusion. Cardiac CT angiography (CCTA) is well suited to assess these non-invasively. We report our consecutive series of non-valvular atrial fibrillation patients who underwent CCTA post-LAA closure with Amplatzer Cardiac Plug (ACP), Amulet (second generation ACP), or WATCHMAN devices. Patients underwent CCTA typically 1-6 months post-implantation. Prospective cardiac-gated CCTA was performed with Toshiba 320-detector or Siemens 2nd generation 128-slice dual-source scanners, and images interpreted with VitreaWorkstation™. GFR <30 mL/min/1.73 m(2) was an exclusion. We assessed for device thrombus, residual LAA leak, device embolization, position, pericardial effusion, optimal implantation, and device lobe dimensions. Forty-five patients underwent CCTA at median 97 days post-LAA closure (18 ACP, 9 Amulet, 18 WATCHMAN). Average age was 75.5 ± 8.9 years, mean CHADS2 score 3.1 ± 1.3, and CHADS-VASc score 4.9 ± 1.6. All had contraindications to oral anticoagulation. Post-procedure, 41 (91.1%) were discharged on DAPT. There was one device embolization (ACP, successfully retrieved percutaneously) and one thrombus (WATCHMAN, resolved with 3 months of warfarin). There were two pericardial effusions, both pre-existing and not requiring intervention. Residual leak (patency) was seen in 28/44 (63.6%), and the mechanisms of leak were readily identified by CCTA (off-axis device, gaps at orifice, or fabric leak). Mean follow-up was 1.2 ± 1.1year, with no death, stroke, or systemic embolism. CCTA appears to be a feasible alternative to transoesophageal echocardiography for post-LAA device surveillance to evaluate for device thrombus, residual leak, embolization, position, and pericardial effusion.